Analisis Hasil Belajar Mata Pelajaran Matematika pada Pembelajaran Online - Rahmawati, Yuvinta Dyah; Meifiani, Nely Indra; Sugiyono, Sugiyono (PGSD STKIP PGRI Pacitan, 2021)
The purpose of this research is to find out: 1) the implementation of mathematics learning in the learning of class V students in SDN 2 Ploso; 2) mathematical learning outcomes on online learning of class V students at SDN 2 Ploso. This research is a qualitative descriptive approach research. This research was conducted in the even semester 2020/2021. The research subject is a student of class V SDN 2 Ploso consisting of 21 students. The results showed that: 1) the implementation of mathematics learning in online learning went well, it was proven that there were 67% of students who scored above KKM; 2) the results of learning mathematics in online learning are based on three cognitive domains of Anderson and Krathwohl including: (a) remembering, 3 students fulfilled the stage of remembering the types and formulations of the volume of cubes and blocks, 2 students increased the lower level of types of shapes; (b) understanding, 2 students understood the stage, 3 students did not understand the known and asked stage; (c) apply, 5 students met the aplication stage.